Re-examining the influence of the inclusion characteristics on the drying shrinkage of cementitious composites. (15th August 2017) - Egan, Galen; Kumar, Aditya; Neithalath, Narayanan; Sant, Gaurav
Highlights: Shrinkage of cementitious mixtures depends on the inclusion dosage, stiffness, and fluid permeability. Shrinkage-moisture loss correlations of cement paste can be used to estimate shrinkage from moisture loss profiles. Abstract: The addition of aggregates to cement paste is known to alter its shrinkage, in relation to the aggregate stiffness and volume fraction. This study reexamines the effects of aggregate volume, and stiffness on shrinkage experienced upon 1 st and 2 nd drying, by cement pastes across a range of w/c (water-to-cement ratio, mass basis). Focus is paid to understand the influence of the volume fraction and properties of inclusions on the shrinkage response. By unifying shrinkage and mass loss relations with sorption isotherms, the moisture transport properties are extracted as a function of drying time and external relative humidity (RH).